2015 IEEE/ACM 37th IEEE International Conference on Software Engineering 2015
DOI: 10.1109/icse.2015.141
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Technology Evaluation Study: Effects of Model-based Analysis and Testing

Abstract: Besides model-based development, model-based quality assurance and the tighter integration of static and dynamic quality assurance activities are becoming increasingly relevant in the development of software-intensive systems. Thus, this paper reports on an empirical study aimed at investigating the promises regarding quality improvements and cost savings. The evaluation comprises data from 13 industry case studies conducted during a three-year large-scale research project in the transportation domain (automot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Model-driven engineering is a large area both in research and practice that is continually evaluated in many studies [9,11,12,15]. What sets this research apart from most evaluations is that we provide a full prototype model-driven solution as open-source software configured for use in a realistic scenario, facilitating immediate experimentation.…”
Section: Related Workmentioning
confidence: 99%
“…Model-driven engineering is a large area both in research and practice that is continually evaluated in many studies [9,11,12,15]. What sets this research apart from most evaluations is that we provide a full prototype model-driven solution as open-source software configured for use in a realistic scenario, facilitating immediate experimentation.…”
Section: Related Workmentioning
confidence: 99%
“…What is not, however, is automatic generation of test scenarios, i.e., model-based testing (MBT). It has been shown that MBT can significantly reduce the effort for testing (Kläs, Bauer, Söderqvist, Dereani, & Helle, 2015) and a number of the presented approaches in the previous section consider it a useful tool for testing autonomous systems. 4.…”
Section: Synopsismentioning
confidence: 99%